1995
DOI: 10.1007/3-540-60392-1_36
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating and refining computational models of spatial relations through cross-linguistic human-subjects testing

Abstract: Abstract. Human-subjects testing based on a sound formal model is outlined as an effective way to evaluate and refine computational models of spatial relations. The cognitive response of a subject (person) to a realworld situation depends on the characteristic of the situation and the characteristics of the subject. Spatial entities can be characterized by topological relations, metric, scale (scope), kinds of phenomena (semantics), motion (time), and (for maps and displays) graphic presentation. Subjects' res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 10 publications
0
24
0
2
Order By: Relevance
“…Claims are often made that qualitative reasoning is akin to human reasoning, but with little or no empirical justification. One exception to this is the study made of a calculus for representing topological relations between regions and lines [138]. Another study is [120] that has investigated the preferred Allen relation (interpreted as a 1D spatial relation) in the case that the composition table entry is a disjunction.…”
Section: Cognitive Validitymentioning
confidence: 99%
“…Claims are often made that qualitative reasoning is akin to human reasoning, but with little or no empirical justification. One exception to this is the study made of a calculus for representing topological relations between regions and lines [138]. Another study is [120] that has investigated the preferred Allen relation (interpreted as a 1D spatial relation) in the case that the composition table entry is a disjunction.…”
Section: Cognitive Validitymentioning
confidence: 99%
“…Some scholars have used these aspects to assist the spatial relation analysis, query and reasoning. Yao and Thill [1] researched how far is far in different contextcontingent; Mark [2], [3], [4] focused on natural language understanding of the spatial relations between lines and regions; Jones [5], [6] researched on build geographical ontology for intelligent spatial search on the web. In China, Xu J [7], [8] researched on natural language understanding of the spatial relations between linear objects; Liu Y [9] focused on representation and reasoning of spatial relations in geographical space; BIAN Fu-ling [10] researched on build location ontology for geographic knowledge base; JING Dong-sheng [11] focused on geo-spatial information semantic expression and service based on ontology.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the dimensionality of the space and objects in question determines the relations that can be used -in a 3D space, relations like BEHIND and IN FRONT OF may be appropriate. In addition to these factors, individual differences like gender (Linn & Petersen 1985) and handedness (Halpern 1986;Mark et al 1995) may affect how one forms mental models of spatial phenomena and assigns meanings to spatial concepts. Anthropologist Hall (1966) found that a subject's experience of space, and hence perception of spatial relations, are affected by culture.…”
Section: Introductionmentioning
confidence: 99%
“…This was confirmed by Montello (1995), in his critical discussion of the significance of cultural differences in spatial cognition. Based on these factors, two human subjects may perceive the same concept quite differently, and hence describe it differently (Mark et al 1994;Mark et al 1995;Worboys 2001). As early as 60 years ago, Whorf and Sapir (1940) proposed that language influences or constrains the way in which people think; this work is known as the Sapir-Whorf hypothesis.…”
Section: Introductionmentioning
confidence: 99%